Ultrasound-based evaluation of the prevalence of abdominal cystic echinococcosis in the Turkestan region of Kazakhstan. (9th September 2021) - Mustapayeva, Aigerim; Luca D'Alessandro, Gian; Doszhanova, Gaukhar; Colpani, Agnese; Sadybekov, Nurbol; Baimakhanov, Zhasulan; Assanov, Ernar; Salybekov, Samat; Kaniyev, Shokan; Serikuly, Erbol; Tagabayeva, Lyazzat; Budke, Christine M; et al.
Abstract: Background: Human cystic echinococcosis (CE) is a zoonotic disease caused by Echinococcus granulosus sensu lato. CE is known to be endemic in some parts of Central Asia. We present findings from an ultrasound-based survey to estimate the prevalence of CE in the Turkestan oblast of Kazakhstan. Methods: In October 2019, six villages were chosen based on records from a national surveillance dataset. Inhabitants aged 5–90 y were invited to undergo a free abdominal ultrasound to screen for CE cysts. All identified cysts were staged according to the WHO-endorsed classification for CE cysts. Results: A total of 2252 individuals underwent ultrasound screening. Twenty-two (0.98%) individuals had CE, with a combined total of 33 cysts: 25 (75.7%) inactive (14 CE4, 11 CE5) and 8 (24.3%) active/transitional (2 CE1, 1 CE2, 3 CE3a, 2 CE3b). One patient had a postsurgical cavity. Sixty-eight patients (3.0%) reported CE prior to surgical treatment. In 25 (36.8%) previously diagnosed patients, albendazole prophylaxis was not used. Conclusions: CE is endemic in the study region, with ongoing transmission. The number of surgically treated CE patients suggests an underestimation of the disease burden by the current surveillance system. Further studies on local CE epidemiology and the implementation of expert treatment recommendations are needed.